Crisis Communication Strategy and Image Restoration for the MBG Program through a Change in BGN Leadership - Dadan Ramdani; Sandy Firman Ramdhani (PT. Student Rihlah Indonesia, 2026)
The Free Nutritious Meals (MBG) Program has faced a crisis of public trust due to implementation and governance issues, highlighting the need for an effective crisis communication strategy to restore the program’s legitimacy. This study aims to analyze the crisis communication strategy of the Indonesian government in restoring the MBG program’s image through the leadership transition at the BGN. The study employed a qualitative approach using directed qualitative content analysis of 30 news articles published by Kompas.id between May 12, 2026 and July 7, 2026. The analysis was conducted using SCCT and IRT frameworks. The findings indicate that the government framed the MBG crisis as a preventable crisis, leading to the dominance of the ‘rebuild’ strategy within SCCT and ‘corrective action” within IRT. These strategies were implemented through the replacement of the BGN leadership, governance reforms, strengthened oversight, policy revisions, and law enforcement support. They were further reinforced by ‘bolstering’, which re-emphasized the MBG program’s strategic objectives. This study’s novelty lies in integrating SCCT and IRT to explain leadership transition as a form of non-verbal crisis communication in the context of public policy. The findings highlight the importance of integrating crisis communication, governance reform, and policy transparency to rebuild public trust in strategic government programs.